Trastuzumab deruxtecan in an elderly patient with HR+/HER2-low breast cancer complicated by pleural effusion: a case report and literature review - Huang, Shiyu; Law, Saikam; Chen, Maojian; Lai, Hongna (Frontiers in Oncology, 2025)
Trastuzumab deruxtecan (T-DXd or DS-8201) is a novel antibody–drug conjugate (ADC) targeting HER2 that has shown significant efficacy in advanced breast cancer. However, data on its use in elderly patients with hormone receptor–positive (HR+)/HER2-low disease complicated by malignant pleural effusion are scarce. We report the case of a 75-year-old woman with HR+/HER2-low (HER2 2+/FISH– at diagnosis, HER2–0 at recurrence) advanced breast cancer who developed multiple lymph node metastases and a large pleural effusion after progression on endocrine therapy plus a CDK4/6 inhibitor. She received trastuzumab deruxtecan as salvage therapy, initially at a reduced dose of 4.4 mg/kg because of frailty, followed by escalation to the standard 5.4 mg/kg dose after good tolerability. Several cycles were administered at extended intervals due to financial constraints. T-DXd therapy resulted in near-complete resolution of the pleural effusion, marked shrinkage of nodal disease, improvement of upper limb edema and respiratory symptoms, and sustained declines in serum tumor markers. Progression-free survival on T-DXd reached 16 months, while overall survival from T-DXd initiation was 18 months. Treatment-related adverse events were limited to mild myelosuppression and gastrointestinal discomfort, without interstitial lung disease. This case suggests that dose-adjusted T-DXd can achieve durable disease control with acceptable safety in a frail elderly patient with HR+/HER2-low breast cancer and pleural effusion, adding to the growing real-world evidence supporting the use of HER2-directed ADCs beyond traditional HER2-positive populations.